Optical-Fiber-Based Smart Concrete Thermal Integrity Profiling: An Example of Concrete Shaft - Ruoyu Zhong; Ruichang Guo; Wen Deng (Advances in Materials Science and Engineering)
Concrete is currently the most widely used construction material in the world. The integrity of concrete during the pouring process could greatly affect its engineering performance. Taking advantage of heat production during the concrete curing process, we propose an optical-fiber-based thermal integrity profiling (TIP) method which can provide a comprehensive and accurate evaluation of the integrity of concrete immediately after its pouring. In this paper, we use concrete shaft as an example to conduct TIP by using the optical fiber as a temperature sensor which can obtain high spatial resolution temperature data. Our method is compared with current thermal infrared probe or embedded thermal sensor-based TIP for the concrete shaft. This innovation makes it possible to detect defects inside of the concrete shaft with thorough details, including size and location. First, we establish a 3D shaft model to simulate temperature distribution of concrete shaft. Then, we extract temperature distribution data at the location where the optical fiber would be installed. Based on the temperature distribution data, we reconstruct a 3D model of the concrete shaft. Evaluation of the concrete integrity and the existence of the potential defect are shown in the paper. Overall, the optical-fiber-based TIP method shows a better determination of defect location and size.